2021
DOI: 10.4081/jphr.2021.2874
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Late-Stage Diagnosis of Breast Cancer among Egyptian Women

Abstract: Background: Detecting Breast Cancer (BC) at earlier stages comes with a better prognosis, while diagnosis at late stages has poor outcomes and escalating mortality rates from the disease. The study aims to understand the factors associated with the latestage diagnosis of BC in Egypt. Design and Methods: A sample of 400 women with a pathologically confirmed BC were enrolled from one of the main tertiary cancer hospitals in Egypt. A cross-sectional study design was conducted. The collected data included: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Contrary to predictions and other studies [3,31], we found that an absence of breast self-examination was associated with an increased chance of early presentation. One of the reasons why these women may appear late is because, unlike a trained doctor, they may miss any mass or change in the breast if they perform breast self-examination using the wrong technique or at the incorrect time.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to predictions and other studies [3,31], we found that an absence of breast self-examination was associated with an increased chance of early presentation. One of the reasons why these women may appear late is because, unlike a trained doctor, they may miss any mass or change in the breast if they perform breast self-examination using the wrong technique or at the incorrect time.…”
Section: Discussioncontrasting
confidence: 99%
“…Earlier research [8,31,32] demonstrated that BC screening behaviours measured by professional breast examination or mammography were related to a lower likelihood of late presentation. At the Breast Disease Treatment Clinic in Sulaimaniyah, regular clinical breast examinations and mammograms are recommended as BC screening measures; therefore, every woman should be aware of this healthcare.…”
Section: Discussionmentioning
confidence: 99%